Orange-fleshed sweetpotato: Strategies and lessons learned for achieving food security and health at scale in Sub-Saharan Africa - Girard, Amy W.; Brouwer, A.; Faerber, E.; Grant, F.; Low, Jan W. (Walter de Gruyter GmbH, 2021)
Against a worsening backdrop of climate stress and population growth, drought-resistant, highly adaptable, nutritious orange-fleshed sweetpotato (OFSP) stands out as a sustainable food crop that supports household resiliency, food security, and health. Recognized as one of the cheapest sources of vitamin A (VA), OFSP holds promise as a food-based approach to combat VA deficiency, a significant public health concern in sub-Saharan Africa. Because the dominant white-fleshed varieties have no beta-carotene, research initiated in the mid-1990s set out to adapt, develop, and promote VA-rich OFSP as a more nutritious alternative to non-OFSP types. Multisectorial strategies that integrate agriculture with health or education sectors hold promise as effective strategies to ensure OFSP reaches and meets the needs of those populations at greatest risk of VA deficiency – pregnant and lactating women, infants, and children. In this article, we share experiences, findings, implementation challenges, and lessons learned from four integrated programs in Kenya, Tanzania, Mozambique, and Ethiopia that aimed to improve the nutrition and health of women and children with production and promotion of OFSP. Across these projects, households significantly increased OFSP production. In all but one, changes in OFSP production were accompanied by improved food security and maternal and child diets.